PsycEXTRA Dataset 2009
DOI: 10.1037/e578572012-007
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Signal Detection Theory for Understanding Driver Behavior at Highway-Rail Grade Crossings

Abstract: We used signal detection theory to examine if grade crossing warning devices were effective because they increased drivers' sensitivity to a train's approach or because they encouraged drivers to stop. We estimated d' and β for eight warning devices using 2006 data from the Federal Railroad Administration's Highway-Rail Grade Crossing Accident/Incident database and Highway-Rail Crossing Inventory. We also calculated a measure of warning device effectiveness by comparing the maximum likelihood of an accident at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…For this reason, drivers’ decision not to comply at the level crossing are also an issue outside peak times. Long level crossing closures during peak hours, such as the ones determined by the present study and reported elsewhere ( 23 ), have been hypothesized as a factor in driver non-compliance ( 41 ). Long waiting times encourage some drivers not to comply at crossings by attempting to traverse a crossing before an approaching train has passed ( 13 , 20 , 21 ).…”
Section: Discussionsupporting
confidence: 55%
“…For this reason, drivers’ decision not to comply at the level crossing are also an issue outside peak times. Long level crossing closures during peak hours, such as the ones determined by the present study and reported elsewhere ( 23 ), have been hypothesized as a factor in driver non-compliance ( 41 ). Long waiting times encourage some drivers not to comply at crossings by attempting to traverse a crossing before an approaching train has passed ( 13 , 20 , 21 ).…”
Section: Discussionsupporting
confidence: 55%
“…Using data from 1986, Raslear reported that the analysis suggested that grade crossing warning devices are effective because they encourage drivers to stop. Yeh, Multer, and Raslear (2009) updated this analysis and compared the findings to more recent data (2006) with similar results. Additionally, the results indicated that warning device effectiveness improved over the 20-year period examined, as drivers behaved more conservatively.…”
Section: Introductionmentioning
confidence: 65%
“…The results by Raslear (1996) and Yeh, et al (2009) demonstrate the improvements in safety at grade crossings, but the analysis does not speak to what led to this improvement. The number of grade crossing accidents decreased by 41% between 1994and 2003(Office of the Inspector General, 2004, a time period in which a number of safety measures were implemented.…”
Section: State Of the Worldmentioning
confidence: 90%
“…A better understanding of these human factors issues not only helps answer why an incident may have occurred but helps prioritize and focus more effective poten tial crash countermeasures. There are two general categories of fac tors that can influence a driver's decision to stop or not stop at a passive level crossing and the probability of an accident occurring: those that affect the driver's ability to detect the presence of a train and those that affect the driver's decision making, or perception of the need to stop (9,10). In human factors terms, these two types of factors can be categorized as "perceptual" and "cognitive."…”
Section: Targeted Literature Reviewmentioning
confidence: 99%
“…Recent research by Yeh and colleagues (10,46,47), as well as previous work by Raslear (48), used signal detection theory to describe and model a driver's decision making at level crossings. Compared to active crossings, passive crossings are associated with the strongest bias for drivers to proceed through the crossing.…”
Section: Information Processingmentioning
confidence: 99%